Cinnamon bark (Cinnamomum cassia) volatile oil extraction using pressurised liquid extraction in comparisson to conventional methods / Nur Ikhfa Musa - Musa, Nur Ikhfa (Faculty of Applied Sciences, 2012)
Cinnamomun cassia is one of the cinnamon bark species was chosen to prepare essential oils by the new method of extraction which is Pressurised Liquid Extraction (PLE) in comparison to the conventional method which is Soxhlet extraction and hydrodistillation to identify and quantify their volatile compound compositions. Cinnamaldehyde was determined to be the highest volatile compound present in the Cinnamomun cassia. Between these three methods, PLE was determined to have the highest yield of cinnamaldehyde (27.58%), followed by Soxhlet (22.43%) and hydrodistillation (0.4%). Gas Chromatography/Mass Spectrometry (GCMS) was used to identify and quantify the volatile compound composition. The result indicated the apparent difference in the volatile compound compositions of essential oil between methods. The total number of volatile compounds identified from the GCMS analysis is 35 compounds. Beside cinnamaldehyde, coumarin was also the main substance found in Cinnamon cassia. In term of concentration, PLE also were determined to have the highest concentration of oil (1390.95 mg/100ml), followed by Soxhlet (1003.95 mg/100ml) and hydrodistillation (905.6 mg/100ml).